The THE INFLUENCE OF PROJECT-BASED LEARNING MODEL ASSISTED BY HOTS-BASED INTERACTIVE STUDENT WORKSHEETS (LKPD) ON CRITICAL THINKING - Farah Yusep Azzahra (SPEKTRA: Jurnal Kajian Pendidikan Sains, 2025)
The project-based learning (PjBL) model, particularly when combined with HOTS-based interactive LKPD, is an effective method for improving critical thinking skills. This study investigates the problem of insufficient critical thinking abilities among students and assesses the impact of the PjBL model supported by HOTS- based interactive LKPD on these skills. Using a quasi-experimental pretest-posttest control group design and basic random sampling, this quantitative research employed HOTS-based assessment tools and analysis techniques to evaluate critical thinking through essay questions. The analysis involved N-Gain tests and independent sample t-tests to measure the enhancement in students' critical thinking abilities. The N-Gain results indicated an improvement of 81.14% in the experimental class (deemed effective) compared to 24.50% in the control class (deemed ineffective). The independent sample t-test showed a significance value of <0.001, which is below 0.05, leading to the rejection of the null hypothesis (Ho) and the acceptance of the alternative hypothesis (Ha). Therefore, the study concludes that the PjBL model, enhanced by HOTS-based interactive LKPD, significantly improves students' critical thinking skills.